Evaluation of Protein Concentration and Limiting Amino Acids Including Lysine and Met + Cys in Prestarter Diet on Performance of Broilers - Mohsen Farkhoy; Mehrdad Modirsanei; Omid Ghavidel; Majid Sadegh; Sadegh Jafarnejad (Veterinary Medicine International)
Four experiments were conducted, in two stages, to evaluate protein and limiting amino acids' (lysine and methionine + cystine) levels in pre-starter diets on broilers’ performance. In each experiment of Stage 1, 640 new-born male Ross 308 cockerels were randomly allocated to eight dietary treatments with a 2 × 4 factorial arrangement. In experiment 1-1, two levels of crude protein (CP: 21% and 23.2%) and four levels of Lys (1.2, 1.3, 1.4, and 1.5%) and in experiment 1-2, two levels of CP (21 and 23.2%) and four levels of Met + Cys (0.85, 0.90, 0.95, and 1.00%) were used. In Stage 2, the optimum levels of Lys and Met + Cys obtained from Stage 1 (1.3 and 1.5% Lys, 0.90 and 1.00% Met + Cys in experiment 1-1 and 1-2, resp.) with two levels of CP (21 and 23.2%) were used in two separate simultaneous experiments with a 2 × 2 factorial arrangement for male and female birds. The levels of CP significantly influenced BWG and FCR in experiment 1-1. Dietary levels of Lys affect BWG (experiment 1-1) and FI (experiments 1-1 and 2-1) significantly. In experiments 1-2 and 2-2, the different levels of Met + Cys did not affect BWG, FI, and FCR of male or female broilers. The results of these experiments indicated that the optimal level of dietary protein and Lys were 23.2% and 1.5%, respectively. Diets with 1% Met + Cys caused optimal performance.